Seasonal variation and effect of non-native invasive vegetation on two bird communities in northeast of Buenos Aires province, Argentina - Palacio, Facundo Xavier (2013)
We studied seasonal patterns and the effect of non-native invasive vegetation on bird communities in woodland and adjacent herbaceous-shrub areas in north-east Buenos Aires province, Argentina. Diversity, species richness and density of bird species were higher in spring and summer than in fall and winter in both habitat types. We also found significant between-habitat differences in bird species composition in winter, spring and summer. Seasonal variations were mainly due to changes in the abundance of migrants, whereas bird species segregation to each habitat was mostly explained by non-native vegetation structure. Most species were associated with sites dominated by either Dipsacus fullonum or Gleditsia triacanthos, whereas only four species were associated with high Ligustrum lucidum densities. These results show that despite the dominance of non-native invasive plant species at our study site, vegetation structure is still the main factor structuring bird communities. In addition, some plant species, such as L. lucidum, seem to have a negative effect on bird communities by reducing their diversity, whereas others, such as D. fullonum and G. triacanthos, seem to have a positive effect compared to L. lucidum by providing not only food resources during a great part of the year but also nest sites.